Investigations On Silver-Copper Nanopaste As Die-Attach Material For High Temperature Applications - Tan , Kim Seah (2015)

(untitled)
A silver-copper (Ag-Cu) nanopaste formulated by mixing Ag and Cu nanoparticles with organic additives (i.e., resin binder, terpineol and ethylene glycol) which is meant for high-temperature die-attach applications has been developed. Various weight percent of Cu nanoparticles (20-80 wt%) has been loaded into the Ag-Cu nanopaste, followed by sintering in open air at temperature of 380°C for 30 min without the need of applied external pressure. The physical, electrical, thermal and mechanical properties were investigated. Both pure Ag and Cu nanopastes were also prepared for comparison purposes. X-ray diffraction results showed that Ag97Cu3, Ag1Cu99, and CuO phases were formed in sintered Ag-Cu nanopaste. Studies revealed that the porosity of sintered Ag-Cu nanopaste increased with an increase of Cu loading, where the presence of porosity has shown its effect in decreasing of density, grain size, electrical conductivity, thermal conductivity and coefficient of thermal expansion (CTE). Although the porosity has also affected the hardness, stiffness and Young’s modulus of sintered Ag-Cu nanopaste, yet an increasing trend has been recorded for aforementioned properties, with the increment of Cu loading. Overall, Ag-Cu nanopaste with 20 wt% of Cu loading has offered the best combination of electrical [2.27 x 105 (Ω-cm)-1] and thermal conductivity [159 W/m-K], where these values are higher than most of the die-attach systems. The low CTE [13 x 10-6/K] that associated with Ag-Cu nanopaste was good to prevent severe buildup of thermal stress between die and substrate. The Ag-Cu nanopaste has demonstrated a melting temperature of 955°C, which enables it to be xxviii considered for high-temperature applications. For metallization and bonding attribute studies, Ag and Au coatings on Cu substrate have displayed the highest (52.6 MPa) and the lowest (34.4 MPa) bonding strength for Ag-Cu nanopaste, respectively. The values of bonding strength were found to have a close relationship with the interface microstructure between Ag-Cu nanopaste and metallization layer on the substrate. Finally, to realize Ag-Cu nanopaste as a high-temperature die-attach material, the Ag-Cu nanopaste was used to attach a silicon carbide (SiC) die on a substrate with either Ag or Au coating. The entire bonding structure has passed a three-cycle thermal aging test at 770°C. The thermal-aged interface microstructure has shown that the Ag-Cu nanopaste was well adherence to SiC die and substrate with Ag coating, but poor adherence to SiC die and substrate with Au coating.